The Impact of Integrated Agricultural Research for Development on Collective Marketing among Smallholder Farmers of Southern Africa - Nyikahadzoi, Kefasi; Siziba, Shepherd; Mango, Nelson; Zamasiya, Byron; Adekunhle, Adenkule Adewale (Asian Journal of Agriculture and Rural Development, 2013)
This article demonstrates how Integrated Agricultural Research for Development (IAR4D) impacts on collective marketing among smallholder farmers of southern Africa through increased crop productivity, yields and income. We use a quasi-experimental design to compare outcomes under IAR4D and under two other states namely conventional approach and non-intervention. The study relies on primary data collected from 665 households during baseline and end line survey. Results from the study show that IAR4D had a positive and significant impact on improving collective marketing in intervention sites as compared to the control sites. In conclusion, the paper demonstrates empirically that collective marketing can help smallholder farmers to reduce barriers to entry into lucrative agricultural markets through IAR4D by lowering transaction costs of accessing input and produce markets. This finding is particularly very important given that middlemen and small traders face huge transaction costs of dealing with many sellers each selling small quantities.